Work-Life Balance and Job Performance among Top Female Bureaucrats in Kwara State Public Service - Lambe , Emmanuel Oyewole; Ishola, Hassan Seyid (Kashere Journal of Politics and International Relations, 2023)
Globalization and bureaucracy has advanced the course of professional work, thereby changing the phase of selection of gender in work. The male and female dichotomy in the Civil service, Education, Engineering and other Professional sector has been reduced. Despite the breakdown in the segregation of the gender bias, a new issue has sprung out, which is the work life balance amongst the top female bureaucrats. The females are embodied with some traditional family responsibility and natural responsibility, still the females have to work and advance their career pursuit. This has overtime constituted a problem for the female genders in the family and in performance at the organization. The objective of the research is to assess the impact of work life balance on female’s employee of Kwara state civil service. The research uses the Spillover theory to explain the impact of work life balance on female’s employee of Kwara state civil service. The research makes use of mixed research method in assessing the impact of the work life balance in Kwara state civil service. The research found out that the male and the female are not been separated in assessing performance that both the males and the females are expected to deliver results, therefore the females are also expected to work hard and also balance the family work relations. The research recommends that adequate family-work relations have to be established in the civil services.